Vascular Health and Gender-Affirming Hormone Therapy: The Immune System in Motion - Jeimison D. Santos; Jefferson Elias-Oliveira; Ualter G. Cipriano; Pedro Vargas-Pinilla; Daniela Carlos; Vania L.D. Bonato; Rita C. Tostes (Arteriosclerosis, Thrombosis, and Vascular Biology, 2026)
Given that fluctuations in sex hormone levels greatly influence cardiovascular homeostasis, this review addresses how gender-affirming hormone therapy impacts vascular function and the immune system, and how these effects may contribute to altered cardiovascular performance in transgender individuals. Gender-affirming hormone therapy alters leukocyte activation and cytokine secretion, that may impact vascular responsiveness, with distinct effects in feminizing and masculinizing regimens. Moreover, gender-affirming hormone therapy–induced changes in the gut microbiome and body composition, together with factors such as sex chromosomes, and environmental stressors may further modulate inflammatory states with potential consequences for cardiovascular health. This review also discusses factors that limit current research, contributing to inconsistent findings and persistent gaps in understanding the cardiovascular and immunologic effects of gender-affirming hormone therapy, along with directions for future studies. Although available data remain limited, understanding these interconnections is essential for optimizing therapeutic strategies, improving cardiovascular health, and fostering more inclusive clinical practices for the transgender community.